Crystal Fields in Nd2Fe14B - COEY, JOHN MICHAEL DAVID (American Physical Society, 1984)
The leading terms in the crystal field at both rare-earth sites in the new permanent magnet alloy Nd2Fe14B are B20 and B22s. The sign of B20 explains the variation of the anisotropy constant K1 reported by Sagawa et al. for the R2Fe14B series. Noncollinear magnetic structures involving the rare-earth sublattices cannot be attributed to second-order crystal-field effects.
PUBLISHED
Keywords: Physics